Measure for Measure: A Thrice Told Tale (KEMANUSIAAN The Asian Journal of Humanities, 2009)
This paper argues that Measure for Measure is a difficult play to perform because it has problematic themes, especially the theme of sexuality, that clash with the way of life and thinking of contemporary society. As such, any director who chooses to stage it must consider these difficulties and how to present them in a natural manner without making the audience feel that the whole production is contrived. The directors of the two major productions discussed in this paper tried their best to present a Measure for Measure that would be acceptable to the modern society. It is evident that there are many interpretations of the Duke and Isabella's characters and also of Isabella's reaction to the Duke's proposal at the end of the play. It can be concluded that no interpretation is wrong because each actor or director brings with him his own reading of the play, and every reading has been influenced by other performances and textual criticisms. Since Measure for Measure is a thematically rich play, it should not be confined to a single interpretation. The different performances of Measure for Measure have proven that theatre is experimental as well as ageless. Because it is a brilliant play with a myriad of interpretations, Measure for Measure will not cease to be a favourite for directors in times to come. It is not wrong to predict that fans of Shakespeare in general and of Measure for Measure in particular can look forward to many more productions.For experienced Shakespeare observers all performances are thrice-told tales. The perceiving eye absorbs the performance even as the mind's eye attends to the text. Both are augmented by the inner ear buzzing with those other voices, both critical and dramatic, carried by the observer into the theatre.(Crowl, Samuel 1992: 3)